A cardanol-based surface-active dithiocarbamate and its application in emulsion polymerization. Issue 1 (April 2019) - Huang, Qinghua; Liao, Haocheng; Hu, Xiuying; Cheng, Chuanjie
Abstract: A surface-active dithiocarbamate is synthesized in three steps from the renewable cardanol. Structures of the intermediates are characterized and confirmed by 1 H-NMR spectra. This functional cardanol-based dithiocarbamate is further used in RAFT emulsion polymerization of vinyl acetate without adding any other emulsifier.